A versatile β-cyclodextrin and polyethyleneimine bi-functionalized magnetic nanoadsorbent for simultaneous capture of methyl orange and Pb(II) from complex wastewater. (February 2019) - Chen, Bo; Chen, Sijiang; Zhao, Huinan; Liu, Yang; Long, Fengxia; Pan, Xuejun
Abstract: Ascribing to their significant differences in physicochemical properties, it is extremely challenging to treat complex wastewater containing more than one class of pollutants via one-step treatment. Here, we focused on disposal of complex wastewater bearing organic dye and heavy metal by using adsorptive method. Thus, by combining the advantages of polyethyleneimine (PEI), β-cyclodextrin (β-CD) as well as Fe3 O4 magnetic nanoparticles, a versatile β-CD and PEI bi-functionalized magnetic nanoadsorbent (Fe3 O4 -PEI/β-CD) with spatially separated sorption sites was successfully constructed for simultaneous capture of methyl orange (MO) and Pb(II) in complex wastewater. In this setting, β-CD cavities and positively charged N-containing groups of PEI were mainly responsible for removal of MO via host-guest inclusion and electrostatic attraction, respectively, and oxygen-bearing groups on the edge of β-CD as well as the free amino moieties in PEI acted as the active sites for Pb(II) uptake. In their individual mono-pollutant system, the adsorption processes can be better described via applying pseudo-second-order kinetic and Langmuir isotherm models. Interestingly, presence of MO in Pb(II)-MO binary system significantly promoted the uptake of Pb(II). But the coexisting Pb(II) had almost no effects on MO uptake. Such results demonstrated that both MO and Pb(II) could be simultaneously and synergistically removed by Fe3 O4 -PEI/β-CD through multiple mechanisms (such as electrostatic attraction, host-guest inclusion, chelating, etc.). Particularly, the excellent regeneration and stability make Fe3 O4 -PEI/β-CD an ideal integrative adsorbent for purification of actual wastewater contaminated by MO and Pb(II). Thus, this study provides some insights into designing a well-performed and easily recyclable adsorbent for simultaneous and synergetic capture of both organic and inorganic contaminants in complex wastewater. Graphical abstract: A versatile β-CD and PEI bi-functionalized magnetic nanoadsorbent with spatially separated sorption sites (denoted as Fe3O4-PEI/β-CD) was successfully constructed for simultaneous removal of methyl orange (MO) and Pb(II) from complex wastewater through multiple mechanisms (such as electrostatic attraction, host-guest inclusion, chelating, etc.). Highlights: A novel dual-functionalized magnetic nanosorbent (Fe3 O4 -PEI/β-CD) is synthesized. As-obtained sorbent can simultaneously remove MO and Pb(II) from model wastewater. Synergistic removal of MO and Pb(II) is from presence of diverse adsorption sites. Resulting adsorbent could be regenerated and reused for model wastewater.